Enhancing the performance of an acetate-fed microbial fuel cell with methylene green - Marcílio, Rafaella; Neto, Sidney Aquino; Ruvieri, Bruno Martins; Andreote, Fernando Dini; de Andrade, Adalgisa Rodrigues [UNESP]; Reginatto, Valeria (Springer Nature, 2021)
Microbial fuel cells are an eco-friendly technology that decontaminate wastewater and generate electricity by the action of exoelectrogenic microbes. However, mechanisms such as bioanode formation and stabilization and the electron transfer mechanism still have to be elucidated and enhanced before this technology can be scaled up for practical applications. Electrochemical characterization showed that a more electroactive biofilm (power density of 77 ± 8 mW m−2) emerged under a charged surface provided by a continuously applied electric current. Among the different molecules evaluated as electron transfer mediator, methylene green was the only molecule that improved cell performance. Methylene green addition increased the cell voltage by 20% and maintained the cell stable for six more days as compared to the control. Bioanode microbial community analysis revealed a high abundance of Arcobacter and Dechloromonas, which may play roles in electricity generation and methylene green discoloration. Microbial fuel cell voltage and stability were increased upon addition of methylene green, which was degraded in the bioanode over time. Identification of microbial members helps to understand MFC performance and to elucidate how methylene green improves MFC stability.
Keywords: Arcobacter; Bioelectro-oxidation; Dechloromonas; Mediator; Thiazine derivative